Leptobrachium smithi Matsui, Nabitabhata, and Panha, 1999 (Anura: Megophryidae), an Addition to the Fauna of Myanmar (Burma) - Das, I.; Chanda, Shyamal Kumar (Asiatic Herpetological Research Society, 2004)
Three specimens of Leptobrachium from the collections of the Zoological Survey of India are identified as Leptobrachium smithi. These specimens were collected by Limborg in 1877. These are the first confirmed records of Leptobrachium smithi for Myanmar.